Participants’ behavioral intention to re-attend outdoor sport events (Penang, Malaysia) / Siew-Ching Yeoh and Yen-Nee Goh - Yeoh, Siew-Ching; Goh, Yen-Nee (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
There have been many outdoor sports events organized in Malaysia every year. Some of the events have turned out to be one of the major attraction among the participants such as the Penang Bridge International Marathon Run where the participants have been re-attending for years. This study examines the influence of physical environmental quality, interaction quality, outcome quality and participant behavioral intention with participants’ satisfaction as the proposed mediator. A total of 100 completed surveys questionnaires was collected through intercepts at major sports events in Penang, Malaysia. Stimulus-organism-response (S-O-R) model is applied in this study to support the proposed research model. Data collected were analyzed using SPSS and Smart PLS. Outcome quality is found to be significantly related to participant behavioral intention. Surprisingly, physical environmental quality and interaction quality were insignificant to participant behavioral intention. Moreover, it was found that participants’ satisfaction mediates the relationship between physical environmental quality, interaction quality, outcome quality and participant behavioral intention. The findings from this study help to sheds some insights to sports events organizers in particular on improving the outcome quality for participants. Moreover, gaining participants’ satisfaction is also important for future re-attend intention.